Plaza adjacent to tall buildings: a thermal comfort refuge in hot humid urban setting - Abdul Majid, Noor Hanita (2000)
Comfortable outdoor spaces are important contributors to sustainable urban design. These thermally comfortable outdoor spaces potentially reduce the needs of providing internal public area such as atrium lobbies, which in turn can contribute to energy conservation. Plazas adjacent to tall buildings, in this instance are one of the many types of outdoor spaces that could provide places of refuge in the hot humid urban areas. The scenario of Kuala Lumpur and micro-climate of the plazas adjacent to tall buildings are presented in this paper. As one of the fastest developing city in the South-East Asia region, Kuala Lumpur experiences the challenges of providing for the physical and social needs. Plazas adjacent to tall buildings that are 'habitable' could be the answer to these needs. This paper also touches on issues of spaces utilization and discusses the cases of local and overseas. Cultural and social effects on space utilization at urban plazas are described to indicate the situation. These aspects are also discussed in conjunction to specific evidences from thermal comfort studies at the plazas adjacent to tall buildings in Kuala Lumpur.